"We are their last chance": A case study of a college basketball environment in an American underserved community - Book Jr., R. T.; Henriksen, K.; Stambulova, N.; Mathorne, O. W. (Journal of Applied Sport Psychology, 2023)
In this case study we used the holistic ecological approach (HEA) to examine an underserved athletic talent development environment (UATDE) in the United States to: (1) holistically describe a successful UATDE—in this case a community college basketball program known as Best Community College, and (2) explore factors contributing to the success of developing athletes that repeatedly earn athletic scholarships. Data were collected via in-situ observations, document analysis, and interviews (both formal and informal) with coaches, players, and other key stakeholders. The findings were summarized in two empirical models: (1) the UATDE empirical model of Best Community College, and (2) the underserved environment success factors (UESF) empirical model of Best Community College. The operation of the UATDE was significantly influenced by the underserved community in which it was embedded, translating to a lack of financial and human resources, while the team`s roster was occupied by athletically talented, but psychosocially vulnerable players. These challenges were overcome, in part, by a dedicated support team as well as the cultural paradigm established by the head coach as a cultural leader. Conclusively, this case study constitutes an important supplementation to the evolving body of literature utilizing the HEA, highlighting how an environmental context can shift the focus of athletic talent development when we consider the concept of a UATDE.